KARAKTERISTIK GABUNGAN KELOMPOK TANI PENERIMA PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (Kasus di Kecamatan Siak Kecil Kabupaten Bengkalis Riau) - Hartati, Susy; Saleh, Amiruddin; Sugihen, Basita Ginting (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Rural Agribusiness Development Program (PUAP) is a program that focuses inreducing poverty and also creating a huge accupation in rural area by providing venturecapital to support on farm and off farm activities. Farmers’ association (Gapoktan) as animplementer of PUAP has a pivotal function to distribute incentives, venture capital, and alsoas the managers of all the programs given. Gapoktan is an association of some farmergroups that collected and worked together for increasing the economic scale and effortefficiency which have several characters. The objectives of this research was to describe thecharacteristic of Gapoktan. This research resulted several important usults, namely: Thecharacteristics were categorized good, where the indicators of norm, the purposes, cohesive,leadership and participation were good categorized, while the indicator of size was lesscategorized, and than Gapoktan were still became a hope for the farmers in increasing anddeveloping their farm activities.